Clinical and economic assessment of anti–epileptic agents in a formular system - Borysenko, N. M.; Bushuieva, I. V.; Hubenko, I. Ya.; Parchenko, V. V.; Бушуєва, Інна Володимирів; Парченко, Володимир Володимирович (My University, 2025)
The article analyzes modern approaches to clinical and economic evaluation of anti–epileptic drugs within the formulatory system. Epilepsy creates a significant socio–economic load that requires rational use of resources. The study substantiates the integration of the principles of pharmacoeconomics and evidence –based medicine to optimize therapy. Formation of lists of basic medicines, in particular the state form of Ukraine is a key mechanism for ensuring the availability and rational use of anti –epileptic drugs. Modern treatment strategies evolve towards a personalized approach, preferring monotherapy with the drugs of the second and third generations. Pharmacoeconomic analysis confirms that generic anti–epileptic drugs reduce costs by 40–50%. Investments in new, expensive treatments can be economically advantageous in the long run by reducing hospitalization and disability costs. Correlation analysis showed that there is a very strong positive relationship between the costs of epilepsy treatment and the country's economic indicators.
Keywords: epilepsy; pharmacoeconomics; formal system; anti–epileptic drugs; clinical and economic assessment; evidence–based medicine; reimbursement